Pengaruh Pendidikan Kesehatan Menggunakan Video Dalam Menurunkan Tingkat Kecemasan Pada Pasien Pre Operasi Hernia - Amilia, Yunita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: to identify the effect of health education using videos in reducing anxiety levels in pre-hernia operation patients Methods: This article is quantitative research using pre-experimental methods. This research uses a one group pre test and post test design, which consists of one group that is given treatment. Anxiety data collection using the HARS scale. Data analyzed is used Wilcoxon test Results: The research showed that the average anxiety score using the HARS questionnaire in pre-hernia surgery patients before being given health education was 2.21 with the lowest value being 1 and the highest being 4. Meanwhile, the anxiety score after being given health education was 0.39 with the lowest value being 0 and the highest being 2. Wilcoxon test results from SPSS output results obtained Asymp.Sig value. 0.000 is less than alpha 0.05 Conclusion: This research shows that health education provided via video can reduce anxiety levels in pre-hernia surgery patient.